The Little Data Book on Financial Development 2015/2016 - World Bank (Washington, DC, 2015)
The Little Data Book on Financial Development 2015/2016 is a pocket edition of the Global Financial Development Database, published as part of the work on the Global Financial Development Report 2015/2016: Long-Term Finance. It contains 39 indicators of financial development in 202 economies, including measures of (1) financial depth, (2) access, (3) efficiency, and (4) stability of financial institutions and markets.